(untitled) (Research Journal Tahqeeqat, 2024)
Hassan Abbasi has emerged as a prominent figure in Pakistani Urdu literature, excelling as a poet, travel correspondent, editor, columnist, organizer and publisher. He is widely regarded as a cornerstone of contemporary poetry, with Asghar Nadeem Syed crediting Atta-ul-Haq Qasmi for discovering his poetic talent. Known for his affable personality and gentle demeanor, Abbasi endeared himself to fellow poets. His focus turned towards Hamdiya poetry, culminating in the publication of "Sahib" in August 2015, which garnered significant acclaim from peers and readers alike. Hamdiya poetry, a rarity in Urdu, is characterized by its unpredictable nature, making Abbasi’s modern approach all the more distinctive.Abbasi skillfully incorporates scenic imagery, rich language, expressive music, symbolism and a balance of brevity and depth, crafting compositions that stand out. Despite not receiving full academic and literary recognition from Urdu scholars and critics, Abbasi’s contributions to Urdu poetry are undeniable, enriching the poetic landscape with an enduring legacy of artistic capital. The influence of classical traditions on Hassan Abbasi’s Hamdiya poetry is seen here and there, but this does not affect his individuality.